“Copy and Paste”: Policy transparency and its influence on the implementation of Electronic Surveillance policies for people deprived of liberty in Peru and Colombia - Espinoza Prado, Gelin Pilar (2024)
This article analyzes the differences in the design and implementation of electronic personal surveillance (EPS) policies in Peru and Colombia, from their first attempts in 2007 to date. Using a comparative political analysis approach, it explores the factors that explain the gap in outcomes, despite the adoption of similar policies. The article uses the theory of policy transfer as a differentiating element: Colombia implemented its policy progressively, relying on pilot projects and making adjustments to the original design according to the results. Peru, on the other hand, in trying to replicate Colombia's initial success, opted for a national implementation without pilot stages, which resulted in a much more limited impact. This process of design by replication of Colombian legislation and direct implementation would have made it difficult for Peru to address the future obstacles of funding, lack of necessary infrastructure and communication of this prison benefit to key actors. Through comparison, this paper shows that prospective design and implementation and the lack of adaptation to national and local realities were the main obstacles to the successful implementation of an EPS policy in Peru. On the other hand, a progressive, flexible and contextualized implementation, as in the Colombian case, allows for more effective results in the application of public policies, even in contexts of low state capacity. Finally, it is noted that the results in Colombia do not have a sufficiently large impact on its public problem to fully qualify as a “success case” in a broader sense, but they do when compared to the insignificant results in Peru.